Thermal analysis of K(x)/La2O3, active catalysts for the abatement of diesel exhaust contaminants - Milt, Viviana Guadalupe (2003)
Potassium loaded lanthana is a promising catalyst to be used for the abatement of diesel exhaust pollutants. In this paper we have combined several thermal techniques to study relevant processes that take place during the soot combustion reaction. Temperature programmed oxidation (TPO) experiments show that with potassium loadings between 4.5 and 10 wt.% and calcination temperatures between 400 and 700 °C, these catalysts mixed with soot give maximum combustion rates between 350 and 400 °C. Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) indicate that the reaction coexists with the thermal decomposition of bulk hydroxide species. For the La2O3 solid, the La(OH)3→LaO(OH) and LaO(OH)→La2O3 processes occur at ca. 360 and 500 °C, respectively, whereas the presence of K in the K(x)/La2O3 catalysts provokes a shift of these endothermic peaks to higher temperatures. In all the studied solids, oxycarbonates decompose in the 550–800 °C temperature range. On the other hand, microbalance results show that the bulk carbonate formation depends on both the potassium content and the calcination temperature. The High Frequency CO2 Pulses technique is useful to study the dynamics of the CO2 adsorption–desorption process and to characterize the surface basicity of the solids. When both La2O3 and K/La2O3 solids are calcined at 700 °C, a strong decrease on the CO2–surface interaction takes place, which correlates with a small decrease in catalytic activity and with an increase in the K/La surface ratio. These effects may be originated, at least in part, by a decrease in oxygen vacancies concentration and a thermal dehydroxylation of the catalysts.